The Nicotiana tabacum ABC transporter NtPDR3 secretes O-methylated coumarins in response to iron deficiency. (8th June 2018) - Lefèvre, François; Fourmeau, Justine; Pottier, Mathieu; Baijot, Amandine; Cornet, Thomas; Abadía, Javier; Álvarez-Fernández, Ana; Boutry, Marc
Abstract : In response to iron deficiency, Nicotiana tabacum secretes both flavins and O -methylated coumarins to the rhizosphere, the latter being transported by NtPDR3, an ABC transporter. Abstract: Although iron is present in large amounts in the soil, its poor solubility means that plants have to use various strategies to facilitate its uptake. In this study, we show that expression of NtPDR3 / NtABCG3, a Nicotiana tabacum plasma-membrane ABC transporter in the pleiotropic drug resistance (PDR) subfamily, is strongly induced in the root epidermis under iron deficiency conditions. Prevention of NtPDR3 expression resulted in N. tabacum plants that were less tolerant to iron-deficient conditions, displaying stronger chlorosis and slower growth than those of the wild-type when not supplied with iron. Metabolic profiling of roots and root exudates revealed that, upon iron deficiency, secretion of catechol-bearing O -methylated coumarins such as fraxetin, hydroxyfraxetin, and methoxyfraxetin to the rhizosphere was compromised in NtPDR3 -silenced plants. However, exudation of flavins such as riboflavin was not markedly affected by NtPDR3 -silencing. Expression of NtPDR3 in N. tabacum Bright Yellow-2 (BY-2) cells resulted in altered intra- and extracellular coumarin pools, supporting coumarin transport by this transporter. The results demonstrate that N. tabacum secretes both coumarins and flavins in response to iron deficiency and that NtPDR3 plays an essential role in the plant response to iron deficiency by mediating secretion of O -methylated coumarins to the rhizosphere.